2004
DOI: 10.2136/sssaj2004.7700
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Capacitance Probe Sensors in a Saline Silty Clay Soil

Abstract: Capacitance probe sensors are a popular electromagnetic method of measuring soil water content. However, there is concern about the influence of soil salinity on the sensor readings. In this study capacitance sensors are calibrated for a saline silty clay soil. An electric circuit model is used to relate the sensor's resonant frequency F to the permittivity (ε) of the soil. The circuit model is able to account for the effect of dielectric losses on the resonant frequency. Dielectric mixing models and empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 32 publications
5
33
0
1
Order By: Relevance
“…3 and 4), where sensors overestimated the VWC even beyond the degree suggested by the intercept. Consistent with these findings are those of Kelleners et al (2004), who reported that the effect of soil salinity on the readings of capacitance probe sensors became apparent at higher VWC. In their study, when capacitance probe sensors were calibrated in a saline silty clay soil, the effect of dielectric losses became apparent at a VWC of 0.31 m 3 m -3 or higher.…”
Section: The Turf Guard Fdr Sensorsupporting
confidence: 85%
See 4 more Smart Citations
“…3 and 4), where sensors overestimated the VWC even beyond the degree suggested by the intercept. Consistent with these findings are those of Kelleners et al (2004), who reported that the effect of soil salinity on the readings of capacitance probe sensors became apparent at higher VWC. In their study, when capacitance probe sensors were calibrated in a saline silty clay soil, the effect of dielectric losses became apparent at a VWC of 0.31 m 3 m -3 or higher.…”
Section: The Turf Guard Fdr Sensorsupporting
confidence: 85%
“…However, in both loamy sand and loam soils, the degree of linearity was greater at low salinity levels than at higher ones, where a quadratic term produced a better fit (not shown) than a linear relationship. As reported by Kelleners et al (2004), at salinity levels from 3 to 12 dS m -1 the fitted calibration equations for a capacitance sensor were linear; however, at 18 dS m -1 the equation required a higher order polynomial regression. Our findings also corroborate those of Inoue et al (2008), who found that the fitted equations obtained for two FDR sensors in a saline sandy soil were linear at low (<4 dS m -1 ) and medium salinity levels (4-10 dS m -1 ), but nonlinear at high salinity levels (>10 dS m -1 ).…”
Section: The Turf Guard Fdr Sensorsupporting
confidence: 56%
See 3 more Smart Citations